KRISIS IDENTITAS MISI GEREJA DI ERA MODERN: TANTANGAN DAN PELUANG - Salaka, Micele Sisiliya (TENTIRO: Jurnal Pendidikan dan Kesehatan, 2025)
The modern era is characterized by rapid social, cultural, and technological changes that significantly influence the Church’s understanding of its identity and mission. This article explores the crisis of missional identity faced by churches as they respond to secularization, pluralism, individualism, and digital advancements. Many churches today struggle to redefine their calling as witnesses of Christ in a rapidly changing world. This study examines key challenges such as loss of relevance, the narrowing of the meaning of mission, and shifts in ministerial focus. However, this crisis also presents opportunities for theological renewal, community strengthening, and the strategic use of digital technology in mission work. Through a contextual and reflective approach, this paper encourages the Church to return to the essence of the Gospel and reposition itself creatively to embody God’s love and truth in contemporary society.